Analisis Elemen Dramatis Game Petualangan Sebagai Media Penyadartahuan Terhadap Satwa - Silviana Ginting; Irfansyah Irfansyah (ULTIMART Jurnal Komunikasi Visual, 2022)
Adventure games are one of the popular game genres that allow the player to simulate being a specific character who is guided through the story followed by exploration and puzzle solving as the main gameplay. Besides being fun, entertaining, and interesting, games are also capable of delivering serious content such as teaching certain lessons or raising awareness of social phenomena, including education and awareness about the existence of animals. This study aims to identify the potential of adventure games as a medium for raising awareness on the issue of animal protection and conservation using dramatic elements in adventure game features. There are two animal themed games studied in this research: Rhino Raid and A Street Cat's Tale. In this study, a comparative analysis of the two games was conducted in the form of descriptive qualitative which was dissected with the theory of dramatic elements in the Playcentric Approach method. The research results and findings are expected to be used as a basis for developing similar games that are used as a medium for education and awareness of animals, especially Indonesian endangered species. Keywords: adventure games; animal awareness; dramatic elements; playcentric.